PENGARUH LATIHAN PUSH UP DAN LATIHAN PULL UP TERHADAP KEKUATAN OTOT LENGAN ATLET BOLA BASKET KLUB OGC (OCEAN GENERATION CLUB) KOTA PADANG - Anton Wahyudin; Fahd Mukhtarsyaf (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The research problem is the lack of arm muscle strength of the OGC Basketball Athletes in the City of Padang. This study aims to determine the effect of push Up and pull Up training on the arm muscle strength of the OGC (Ocean Generation Club) Club Basketball City of Padang. This type of research is quantitative research with an experimental approach. The population in this study was the population in this study were all athletes enrolled in the OGC Club of the City of Padang who were actively practicing until now totaling 30 people. The sampling technique is purposive sampling technique. then, the sample in this study is the male athletes of the City of Padang OGC Club, amounting to 15 people. Data collection was carried out by pre-test and post-test the muscle strength of the arm of the OGC (Ocean Generation Club) Club of the City of Padang using a push strength test. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05. From the data analysis performed the results obtained: There is an effect of the Push Up and Pull Up exercises on the muscle strength of the arm of the OGC Basketball Club (Ocean Generation Club) in Padang City, with the acquisition of the test coefficient